Еволюція екситонного спектру у триямній закритій циліндричній квантовій точці при безмежному зростанні висот двох зовнішніх квантових точок - Ткач, М.; Маханець, О.; Довгонюк, М.; Цюпак, Н. (Праці наукового товариства ім. Шевченка, 2011)
Within models of the effective masses and rectangular potentials the exciton energy spectrum in cylindrical closed nanoheteosystem is investigated at the infinite increase of the heights of two outer quantum dots. The principle ability of approximating the two barrier open system by three well closed system is proven. This makes it possible to obtain the exciton binding energy in open systems .